SIRT1 activating compounds reduce oxidative stress and prevent cell death in neuronal cells - Khan, Reas S.; Fonseca-Kelly, Zoe; Callinan, Catherine; Zuo, Ling; Sachdeva, Mira M.; Shindler, Kenneth S. (Frontiers in Cellular Neuroscience, 2012)
Activation of SIRT1, an NAD+-dependent deacetylase, prevents retinal ganglion cell (RGC) loss in optic neuritis, an inflammatory demyelinating optic nerve disease. While SIRT1 deacetylates numerous protein targets, downstream mechanisms of SIRT1 activation mediating this neuroprotective effect are unknown. SIRT1 increases mitochondrial function and reduces oxidative stress in muscle and other cells, and oxidative stress occurs in neuronal degeneration. We examined whether SIRT1 activators reduce oxidative stress and promote mitochondrial function in neuronal cells. Oxidative stress, marked by reactive oxygen species (ROS) accumulation, was induced in RGC-5 cells by serum deprivation, or addition of doxorubicin or hydrogen peroxide, and resulted in significant cell loss. SIRT1 activators resveratrol and SRTAW04 reduced ROS levels, and promoted cell survival in RGC-5 cells as well as primary RGC cultures. Effects were blocked by SIRT1 siRNA. SIRT1 activators also increased expression of succinate dehydrogenase, a mitochondrial enzyme, and promoted deacetylation of PGC-1α, a co-enzyme involved in mitochondrial function. Results show SIRT1 activators prevent cell loss by reducing oxidative stress and promoting mitochondrial function in a neuronal cell line. Results suggest SIRT1 activators can mediate neuroprotective effects during optic neuritis by these mechanisms, and they have the potential to preserve neurons in other neurodegenerative diseases that involve oxidative stress.